Tax Avoidance: The Moderating Role of Profitability - Putri Widyaningrum; Indah Hapsari (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
This study aims to determine the effect of transfer pricing and leverage on tax avoidance, with profitability as a moderating variable. The object of this study is healthcare sector companies listed on the Indonesia Stock Exchange in the 2018-2022 period. The health sector has an important role, especially during the early and peak periods of the pandemic, and companies are not only required to support health, but also to prioritize company performance, including financial and tax aspects. Based on purposive sampling, the sample of this study was 130 company data from a total population of 150 company data in the healthcare sector. The testing method used in this study used multiple linear regression analysis and absolute difference value tests. The absolute difference test is used to answer moderation problems. The results of the study indicate that: (1) transfer pricing has an effect on tax avoidance; (2) leverage has an effect on tax avoidance; (3) profitability cannot moderate the effect between transfer pricing and tax avoidance; and (4) profitability cannot moderate the effect between leverage and tax avoidance. Profitability that cannot moderate indicates that companies as corporate taxpayers do not correlate profitability and tax burden significantly, considering the many tax facilities borne by the government and even exempted from taxation, especially in sectors that contribute to overcoming Covid-19 outbreak (including the healthcare sector). However, the influence of transfer pricing and leverage on tax avoidance indicates that taxpayers must remain cautious in the treatment of special relationships and debt policies, which require full disclosure of special relationship activities and reasonable debt limits to avoid the potential risk of tax audits.